Treatment of calcaneal fractures - Popelka, Vladimír (Grada, 2018)
The textbook presents a chronological overview covering anatomy, biomechanics, diagnostics, classifications, followed by clinical chapters on individual operative techniques of treatment of calcaneal fractures. Each chapter reflects author's personal clinical experience and views.
Keywords: Chirurgie, ortopedie, traumatologie